Japanese labour and management in transition diversity, flexibility and participation - Sako, Mari; Sato, Hiroki (Routledge LSE, 1997)
This study considers the future of industrial relations in Japan in the face of increasing economic pressures. It outlines recent trends in Japanese labour markets, labour law and corporate strategy and examines the changing interaction between the state, management and labour.